Framtidsfullmakter i praktiken - Blev det som tänkt? - Lavré,Filippa (2024)
In connection with the development of legal practice regarding future powers of attorney in recent years, some questions have been raised about whether the use of the power of attorney works in practice. In 2017, the Act (2017:310) on future powers of attorney, LFF, was adopted with the aim of functioning as a complement to the existing system of guardianship and trusteeship in the parental code, FB (1949:381). The purpose of the future power of attorney is to give individuals the opportunity to decide over their personal and financial affairs by establishing a future power of attorney with a selected power of attorney who becomes responsible when he becomes incapacitated. The new type of power of attorney is intended to strengthen the individual's self-determination and integrity by assigning the possibility of establishing a power of attorney that will be effective in the future. The LFF regulates, among other things, the future power of attorney's form requirements, establishment and entry into force. As powers of attorney for the future have been drawn up and used, questions of interpretation have arisen which means that one should consider changing the LFF in certain respects. When the thoughts and considerations put forward in the bill do not have full impact in the practical application, as nowadays in certain situations it will still be required that a good man be appointed, then a change in the legal text should be considered. The legal cases described in the essay result in a discussion where advantages and disadvantages are weighed against each other. The reasons for the government's bill seem to have ended up in obscurity in connection with the various bodies' interpretation of the wording of the law, and jurisprudence is therefore emerging in step with time. Through Lantmäteriet's interpretation of the law, practice has been created around what they consider to be an equal situation and conflicting interest, and this has a clear effect on relatives who want to use a power of attorney for the future. The essay gives a clear picture of the pros and cons of power of attorney for the future in practice, and focuses on the parts where family members want to use the power of attorney to manage the affairs of the incapacitated person.
Keywords: Civilrätt (en. private law); Framtidsfullmakt; Fullmakt; Beslutsoförmåga